Inflammatory markers as potential mediators on the negative association between training load and bone mineral density in adolescent competitive swimmers: ABCD-growth study - Agostinete, Ricardo R. [UNESP]; Narciso, Pedro H. [UNESP]; Coelho-e-Silva, Manuel João; Bielemann, Renata M.; Gobbo, Luis Alberto [UNESP]; Turi-Lynch, Bruna Camilo; Fernandes, Romulo Araújo [UNESP]; Vlachopoulos, Dimitris (Frontiers, 2025)
Introduction: Competitive swimming during adolescence has been linked to poor bone development, potentially influenced by training load, inflammation, hormones, and bone markers. However, this influence has been poorly investigated in the literature. Objective: To compare whether competitive adolescent swimmers present differences in inflammatory, immunological, anabolic, and bone markers compared with non-sport group and to analyse whether inflammatory variables mediate the association between training load and areal bone mineral density (aBMD) in the swimmers group. Methods: This cross-sectional study included 61 adolescents (20 females, 15.4±2.3 years), of which 30 were adolescent swimmers and 31 did not participate in sports (non-sports group). The daily training load was obtained by multiplying the perceived exertion score by the training volume of the swimmers. Lean soft tissue, fat mass and aBMD were estimated from whole-body scans using dual-energy X-ray absorptiometry and peak height velocity considering stature and body mass. Blood samples were collected to assess bone markers (calcium, 25-hydroxy vitamin D, C-terminal telopeptide, and osteocalcin), growth hormones, insulin-like growth factor 1 (IGF-1), lymphocytes, leukocytes, and inflammatory markers (interleukin-6 [IL-6] and C-reactive protein [CRP]). Statistical analyses applied a significance level at p<0.05. Results: Besides lower values in BMD (expect in upper limbs), swimmers had higher calcium (10.0 ± 0.30 vs 9.7 ± 0.44, p=0.007), vitamin D (42.6 ± 10.4 vs 24.2 ± 5.9, p<0.001), and IGF-1 (397.2 ± 115.1 vs 220.3± 73.9, p<0.001) concentrations than their non-sports peers. The mediation analysis found no indirect associations between training load and aBMD through inflammatory markers. Nevertheless, training load was directly and negatively associated with aBMD in the lower limbs (β=-0.1533, 95%CI:-0.2875, -0.0191) and total body less head (β=-0.0978, 95%CI:-0.1880, -0.0076) through IL-6 and directly and negatively associated with aBMD at all sites through CRP. Conclusion: The swimming and non-sports groups did not show differences in bone, inflammatory, or immunological markers. In contrast, swimmers had higher concentrations of IGF-1, calcium, and 25-hydroxy vitamin D. Although the training load was negatively associated with aBMD, inflammatory markers (IL-6 and CRP) did not mediate this association. Reinforcing the hypothesis that swimmers have lower aBMD due to the hypogravitational environment.